Religious Conversion in Hadith and the Discourse of Muslim Scholars - Muttaqin, Zaenal; Sarib, Suprijati; Husain, Husain; Rahman, Rahman; Rohmah, Siti; Mokodenseho, Sabil (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to analyze the status of hadiths that serve as the basis for the imposition of sanctions on individuals who convert from Islam to other beliefs (apostasy) and the views of Muslim scholars in understanding the legal messages behind hadiths on apostasy. This study addresses questions regarding the wording, transmission, and status of hadiths on apostasy, as well as how Muslim scholars define apostasy and interpret the legal messages of apostasy sanctions in the hadiths of the Prophet. The study utilizes the method of takhrij hadith with an analytical-descriptive approach. Both primary and secondary research data are gathered from various literary sources. The study finds that hadiths on the legal sanctions for apostasy have two forms of wording: